Pengaruh Kualitas Pelayanan, Citra Merek, dan Promosi terhadap Loyalitas Nasabah pada PT Bank Central Asia Tbk (BCA) - Shakira Benanti; Jamaludin Khalid (AKSIOMA : Jurnal Manajemen, 2026)
This study aims to examine the influence of service quality, brand image, and promotion on customer loyalty at PT Bank Central Asia Tbk (BCA). A quantitative approach was employed using primary data collected through questionnaires distributed to 100 respondents selected using an accidental sampling technique. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25, supported by validity and reliability tests, classical assumption tests, F-test, t-test, correlation analysis, and coefficient of determination. The results indicate that, simultaneously, service quality, brand image, and promotion have a significant effect on customer loyalty. Partially, brand image and promotion have a significant effect, while service quality does not have a significant effect on customer loyalty. The coefficient of determination shows that 69.8% of customer loyalty is explained by these variables, while the remaining 30.2% is influenced by other factors. These findings suggest that strengthening brand image and optimizing promotional strategies are more effective in enhancing customer loyalty, while improvements in service quality need to be more consistent and aligned with customer expectations to create a stronger impact.